EDUCATIONAL EXPERIENCES AND TRAJECTORIES OF COGNITIVE FUNCTIONING AMONG MID-LIFE AND OLDER U.S. ADULTS - Walsemann, K (Innov Aging, 2018)
Educational attainment is associated with better cognitive functioning among older adults, but significant variation in educational experiences exist even at equivalent levels of educational attainment. We examine if educational content (i.e., college prep curriculum, involvement in language or creative arts), school context (i.e., class size in elementary school, attendance at majority non-White elementary school), and academic ability (i.e., self-reported reading and math ability, learning problem) are associated with trajectories of cognitive functioning, independent of educational attainment among mid-life and older US adults. We use data on educational experiences from the 2015 Health and Retirement Study Life History Mail Survey (LHMS), restricting our sample to age-eligible LHMS respondents who provided cognitive functioning at least once between 1998 and 2014, and attended primary school or higher (n=6,056 respondents providing 38,452 person-period observations). At age 65, all of the educational experiences included in the model were significantly associated with cognitive functioning, independent of educational attainment. For example, a small class in elementary school and involvement in language or creative arts in high school were positively associated with cognitive functioning at age 65, whereas lower self-reported reading and math ability at age 10 were inversely associated with cognitive functioning. Educational experiences were unrelated to rate of cognitive decline. Additionally, educational experiences were more strongly associated with cognitive functioning among recent cohorts. Identifying which educational experiences affect cognition in older adulthood, and if the impact of these educational experiences differs across cohorts, can clarify which aspects of education are important for cognitive health.